Exploring the Interplay Between Fintech Utilization and Cyber Security Awareness - TP, Jisha; Sumathy, M. (Formosa Journal of Computer and Information Science, 2024)
To examine the impact of fintech on cyber security awareness. here the study examines the variables trust, self-efficacy and frequency of using fintech have any role in enhancing the cyber security awareness among the customers. in the study, the researcher collected primary data with the help of a questionnaire and secondary data from different magazines, articles and newspapers. Then the researcher used correlation coefficient, regression and ANOVA to analyse the data. The study found that self-efficacy can enhance cyber security awareness among customers and that trust also contribut8i8ng to the creation of awareness but the frequency of using fintech doesn’t have much impact on cyber security awareness. then the study also found that the frequency of using fintech does not have any significant difference across the different age groups but self-efficacy and trust have significant differences. The outcome of the study can be used by the fintech companies to understand how to enhance the awareness of cyber security among the customers. The company can make policies and facilitate services to enhance the trust and self-efficacy among the customers because those factors contribute to cyber security awareness. through enhancing cyber security companies and customers can eliminate information theft by hackers